Subordination of Civil Cases: Theoretical Rules and Practical Problems - Normurotovna, Esanova Zamira (Indonesian Journal of Law and Justice, 2024)
This article is devoted to the topic of subordination, which is one of the oldest and most relevant institutions of civil procedural law, the content of this topic includes which body is competent to consider disputes (cases), its criteria and conditions, as well as the limits of the competence of the court and other bodies in this area. The task of subordination in a broad sense determines the forms of protection (judicial or extrajudicial resolution) of the rights and interests of individuals (individuals and legal entities). In a narrow sense, it is understood to belong to a number of state bodies and organizations empowered to protect violated and disputed subjective rights of individuals and legal entities and their legally protected interests. The subordination of cases plays a key role in delineating their powers from each other. The article also includes aspects of subordination, which is a broad concept in relation to jurisdiction, similarities and differences with this procedural institution. At the same time, the article provides detailed information and analysis of several types of subordination in civil procedural law, including alternative, contractual, imperative and exceptional types. At the end of the article, problems related to the topic of subordination, suggestions and recommendations for their solution, and the author's conclusions are presented.